Comprehensive Genome-Wide Identification and Expression Profiling of Eceriferum (CER) Gene Family in Passion Fruit (Passiflora edulis) Under Fusarium kyushuense and Drought Stress Conditions - Rizwan, Hafiz Muhammad; Waheed, Abdul; Ma, Songfeng; Li, Jiankun; Arshad, Muhammad Bilal; Irshad, Muhammad; Li, Binqi; Yang, Xuelian; Ali, Ahmad; Ahmed, Mohamed A. A.; Shaheen, Nusrat; Scholz, Sandra S.; et al. (Frontiers in Plant Science, 2022)
Plant surfaces are covered with cuticle wax and are the first barrier between a plant and environmental stresses. Eceriferum (CER) is an important gene family involved in wax biosynthesis and stress resistance. In this study, for the first time, 34 CER genes were identified in the passion fruit (Passiflora edulis) genome, and PeCER proteins varied in physicochemical properties. A phylogenetic tree was constructed and divided into seven clades to identify the evolutionary relationship with other plant species. Gene structure analyses revealed that conserved motifs ranged from 1 to 24, and that exons ranged from 1 to 29. The cis-element analysis provides insight into possible roles of PeCER genes in plant growth, development and stress responses. The syntenic analysis revealed that segmental (six gene pairs) and tandem (six gene pairs) gene duplication played an important role in the expansion of PeCER genes and underwent a strong purifying selection. In addition, 12 putative ped-miRNAs were identified to be targeting 16 PeCER genes, and PeCER6 was the most targeted by four miRNAs including ped-miR157a-5p, ped-miR164b-5p, ped-miR319b, and ped-miR319l. Potential transcription factors (TFs) such as ERF, AP2, MYB, and bZIP were predicted and visualized in a TF regulatory network interacting with PeCER genes. GO and KEGG annotation analysis revealed that PeCER genes were highly related to fatty acid, cutin, and wax biosynthesis, plant-pathogen interactions, and stress response pathways. The hypothesis that most PeCER proteins were predicted to localize to the plasma membrane was validated by transient expression assays of PeCER32 protein in onion epidermal cells. qRT-PCR expression results showed that most of the PeCER genes including PeCER1, PeCER11, PeCER15, PeCER17, and PeCER32 were upregulated under drought and Fusarium kyushuense stress conditions compared to controls. These findings provide a foundation for further studies on functions of PeCER genes to further facilitate the genetic modification of passion fruit wax biosynthesis and stress resistance.